Observed life history endpoints of Folsomia candida depending on the Break-Thru® S 301 soil concentration - Jonas Fischer; Borbala Szabo; Leonid Manikhin; Juliane Filser (PANGAEA, 2025)
The life history data set contains the observed life history endpoints of F. candida depending on the respective Break-Thru® S 301 soil concentration in mg/kg dry soil. The recored life history endpoints are the counted number of juveniles, the hatching success in %, the calculated reproductive investment, the egg size in mm and the egg number. The test was conducted in soil S, with water as solvent and flotation a sextraction method.
In: Fischer, J et al. (2025): The impact of the surfactant Break-Thru® S 301 on the recovery of springtail Folsomia candida juveniles in OECD 232 reproduction test by different extraction methods [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.982928